A critical examination of the concept of welfare dependency: its assumptions, underlying values and manifestation in social policy, internationally and in South Africa - Di Lollo, Adrian (Department of Social Development, 2024)
[page 38, 54, 81 missing, page 97 duplicated] Concern over "welfare dependency" has featured prominently in the public discourse around social assistance programmes in numerous countries for many years. The notion that social assistance payments tend to sap the recipient's initiative, independence and propensity for securing paid employment is widespread and is often assumed to be an objective fact (rather than a concept) by public officials, social commentators and the media. Consequently, charges of "welfare dependency" have often been used as the basis for cutting social assistance expenditure, restricting eligibility or preventing new initiatives. In South Africa, for example, the concept has been used in opposition to developing a universal Basic Income Grant (BIG). With the aid of case studies focusing on recent social welfare developments in South Africa, Australia and Brazil, this study attempts to critically analyse the term "welfare dependency" to determine which social values and assumptions inform the concept. In addition, the study aims to determine how "welfare dependency" manifests in contemporary social welfare policy and, most importantly, determine if the utilisation of the concept is related to other socio-economic agendas.